Archaeological survey in the Blue Nile area, Central Sudan. Prospección arqueológica en el área del Nilo Azul, Sudán Central - Fernández, Víctor M.; Jimeno, Alfredo; Menéndez, Mario; Lario, Javier (Complutum, 2003)
The results are presented of an intensive survey of the Wadi Soba-el-Hasib area east of Khartoum on the east bank of the Blue Nile and the exploration of the Blue Nile Basin upstream to Singa. The survey focused mainly on the Prehistoric sites, with the Mesolithic period (Early Khartoum) as the mostly represented with more than 80% of the discovered sites, the Neolithic sites (Shaheinab-Jebel Moya) making up most of the remainder 20%. Very few Palaeolithic sites were recorded. Late Neolithic sites of large size have been found for the first time in the Central Sudan, all of them located away from the Blue Nile in the Butana and Gezira plains. Site structure and formation processes, ceramic seriation and settlement patterns have been analysed applying statistical multivariate methods to the survey quantitative data. Some historical trends have been noticed. The first is the change from a Nilewadi aquatic exploitation by small mobile groups towards demographic concentration of near-sedentary savanna hunting herding populations. During the Late Neolithic period the groups adopted a mobile economy and their only archaeological record thereafter are the burial tumuli fields up to the Christian and Islamic periods.